HPV-Vaccines - Calagna, Gloria (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Human papillomavirus (HPV) is closely linked with the pathogenesis of cervical cancer and many other cancers. HPV vaccines are vaccines that prevent infection from certain types of human papillomavirus. However, despite the various prevention strategies and treatments, such as HPV screening, prophylactic HPV vaccines, surgery, radiotherapy, and chemotherapy, the disease burden remains heavy worldwide. Currently, three types of prophylactic vaccines-quadrivalent HPV vaccines, bivalent HPV vaccines, and a new nonavalent HPV vaccine-are commercially available. Although these vaccines protect against 90% of HPV infections, their capacity to eliminate pre-existing infections is limited. In this Topical Collection, we aim to systematically cover the progress, current status, and future prospects of various vaccines being developed for the prevention and treatment of HPV-associated lesions and cancers.